Moderasi Beragama di Era Algoritma: Tantangan Epistemologis dan Implikasinya bagi Pendidikan Islam Generasi Z - Trian Hermawan; Jamal Fakhri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The rapid expansion of algorithm-driven digital media has significantly transformed how religious knowledge is produced, accessed, and internalized by young generations. Within Islamic education, this transformation presents epistemological challenges to the cultivation of religious moderation, particularly among Generation Z, whose learning practices are deeply embedded in social media ecosystems. Existing studies on religious moderation in Islamic education largely adopt normative and policy-oriented perspectives, while paying limited attention to the epistemic processes through which learners construct religious understanding in algorithmic environments. This article aims to analyze recent scholarly trends (2020–2025) on religious moderation, Islamic education, algorithms, and Generation Z, and to reconstruct religious moderation as an epistemic competence within Islamic educational practice. The study employs a qualitative narrative literature review strengthened by descriptive analysis of Scopus metadata to identify dominant themes and research gaps across interdisciplinary literature. The findings indicate a substantial gap between the growing body of research on Islamic education and Generation Z and the limited integration of algorithmic structures and epistemological dimensions of religious moderation. The study argues that algorithmic personalization shapes the visibility, authority, and fragmentation of religious knowledge, thereby influencing how moderation is learned and practiced. As a conceptual contribution, this article proposes reframing religious moderation as an epistemic learning competence grounded in Islamic epistemology, critical digital literacy, and algorithmic awareness. This framework offers theoretical and practical implications for curriculum development, pedagogical design, and the management of Islamic educational institutions in the digital era.